Auditive discrimination of equine gaits by parade horses (2009)
The purpose of this study was to examine parade horses' auditory discrimination among four types of equine gaits: paso-fino ('fine step'), trote-reunido ('two-beat trot'), trocha ('trot'), and galope-reunido ('gallop'). Two experimentally naïve horses were trained to discriminate the sound of their own gait (paso-fino or fine step), through an experimental module that dispensed food if the subject pressed a lever after hearing a sound reproduction of a particular gait. Three experimental phases were developed, defined by the period of exposure to the sounds (20, 10, and 5 seconds, respectively). The choice between pairs of sounds including the horse's own gait (fine step and two-beat trot; fine step and gallop; and fine step and trot) was reinforced differentially. The results indicate that the fine step horses are able to discriminate their own gait from others, and that receptivity to their own sounds could be included in their training regime.